2017
DOI: 10.1161/jaha.116.005146
|View full text |Cite
|
Sign up to set email alerts
|

Use of p53‐Silenced Endothelial Progenitor Cells to Treat Ischemia in Diabetic Peripheral Vascular Disease

Abstract: BackgroundPeripheral vascular disease is a major diabetes mellitus‐related complication. In this study, we noted that expressions of proapoptotic p53 gene and its downstream cascade gene such as p21 are upregulated in hyperglycemia. Therefore, we investigated whether p53‐ and p21‐silenced endothelial progenitor cells (EPCs) were able to survive in hyperglycemic milieu, and whether transplantation of either p53 knockout (KO) or p21KO or p53‐ and p21‐silenced EPCs could improve collateral vessel formation and bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…This is concurrent with reduced inflammatory and apoptosis cascade markers such as IL6 and Caspase-3 mRNA expressions in CD34− cells indicating an overall reduction in inflammation and apoptosis pathway, which could be secondary to upregulation in antioxidants. This is particularly interesting as there is sufficient evidence from our previous work, to suggest significant patho-physiological role of ROS (anti-oxidant expression may increase in response to increased intracellular ROS presence) in not only EPCs but also in MSCs in a setting of hyperglycemia, as seen in diabetes [ 10 , 39 ]. The decrease of IGF-1 mRNA expression in CD34− cells in the saxagliptin intervention group compared to placebo may indicate reduced insulin resistance at the levels of MNCs, which also supports reduction of cellular inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is concurrent with reduced inflammatory and apoptosis cascade markers such as IL6 and Caspase-3 mRNA expressions in CD34− cells indicating an overall reduction in inflammation and apoptosis pathway, which could be secondary to upregulation in antioxidants. This is particularly interesting as there is sufficient evidence from our previous work, to suggest significant patho-physiological role of ROS (anti-oxidant expression may increase in response to increased intracellular ROS presence) in not only EPCs but also in MSCs in a setting of hyperglycemia, as seen in diabetes [ 10 , 39 ]. The decrease of IGF-1 mRNA expression in CD34− cells in the saxagliptin intervention group compared to placebo may indicate reduced insulin resistance at the levels of MNCs, which also supports reduction of cellular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, endothelial progenitor cells (EPCs, defined here as CD34+ cells), which are specialized cells responsible for endothelial repair and neo-angiogenesis, play an important role in diabetes. It has been shown that EPCs are impaired in number, function and gene expression in hyperglycemia and diabetes related complications [ 6 10 ]. Moreover, it has been reported that EPCs (CD34+) from diabetic patients failed to incorporate and repair damaged vessels [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model of hypertension-hypercholesterolemia, the administration of EPCs reduced hepatic lipid accumulation and consequently alleviated hypertension and dyslipidaemia [26]. In contrast, Silvestre et al found that EPC treatment aggravated the atherosclerosis burden when EPCs were transferred from young to old ApoE −/− mice [7]. Therefore, the results of prior atherosclerosis studies conflict in terms of both the potential benefits and adverse outcomes of EPC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the potential therapeutic effects of EPCs on hyperlipidaemia-associated kidney damage have not been addressed. A previous study in an acute kidney injury model found that administration of EPCs enhanced microvascular endothelial regeneration and protected against kidney fibrosis [5]; however, Silvestre found that EPC treatment augmented the lesion burden when EPCs were transferred from young to old ApoE −/− mice [7]. These therapies are still controversial and inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that high glucose environment, as seen in diabetes mellitus (either type 1 or 2), leads to functional impairment of circulating EPCs. Their number goes down, along with their ability to form colonies and migration to the site of endothelial damage [6][7][8][9][10]. Other studies have shown that healthy CD34 + cells can effectively repair damaged endothelial cell lining [11].…”
Section: Introductionmentioning
confidence: 99%